2004
DOI: 10.1086/422766
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Endothermic Ancestors of Crocodiles at the Stem of Archosaur Evolution

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. ABSTRACT Physiological, anatomical, and developmental features of the crocodilian heart support the paleontological evidence that the ancestors of living crocodilians were act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
147
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(157 citation statements)
references
References 102 publications
5
147
0
Order By: Relevance
“…Such an interpretation then makes endothermy a character for the Archosauria. The presence of pterosaurs from high-paleolatitude settings (Alaska and New Zealand) is consistent with the implication of Seymour et al (2004) that pterosaurs, as members of the Archosauria, were endothermic. Recently the skeletons of large pterosaurs have been shown to have increased appendicular pneumaticity and this may have aided in thermoregulation (Claessens et al, 2009).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Such an interpretation then makes endothermy a character for the Archosauria. The presence of pterosaurs from high-paleolatitude settings (Alaska and New Zealand) is consistent with the implication of Seymour et al (2004) that pterosaurs, as members of the Archosauria, were endothermic. Recently the skeletons of large pterosaurs have been shown to have increased appendicular pneumaticity and this may have aided in thermoregulation (Claessens et al, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…The Archosauria includes the Crocodylia, Pterosauria, and Dinosauria, suggesting at least two physiological strategies within this major taxonomic group, with some suggestion that pterosaurs were endothermic (Lu et al, 2005). In a recent study, Seymour et al (2004) suggested that modern crocodiles are secondarily ectothermic and that ancestral forms were endothermic. Such an interpretation then makes endothermy a character for the Archosauria.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why some pseudosuchians grow faster than others, however, remains unclear. Possible triggers for fast growth in Batrachotomus might be in response to environmental parameters (Botha-Brink and Smith, 2011;Botha-Brink et al, 2016), respiration and metabolic rates (Cubo et al, 2012;Seymour et al, 2004), large body size , a possible earlier onset of sexual maturity (Karkach, 2006), or an erect stance combined with an active predatory life style (Benton, 1984;Seymour et al, 2004). For instance, in an unstable environment, fast growth and earlier maturity may have been favorable , which is in agreement with the supposed habitat of Batrachotomus.…”
Section: Discussionmentioning
confidence: 76%
“…Although monitor lizards are ectotherms, their lifestyles are largely convergent with small predatory mammals (15) and they have high aerobic capacities compared with other lizards (16). In contrast, extant alligators have limited aerobic stamina (17) but their common ancestor with birds may have had a great aerobic capacity (18) or may have been endothermic (19,20). Crocodilians and monitor lizards also share a suite of features of their pulmonary and cardiac anatomy that have been purported to give rise to, or coevolve with, birdlike patterns of flow.…”
mentioning
confidence: 99%